Indonesia’s Strategy to Face China’s Aggressiveness in the North Natuna Sea: A Defense Policy Perspective 2014–2023 - Ristu Tri Hastawan; Muradi Muradi; Yusa Djuyandi (Yayasan Sembilan Pemuda Indonesia, 2026)
This research aims to identify the forms of China’s aggressiveness, analyze how Indonesia formulated and implemented its defense politics, and assess the effectiveness of such responses in safeguarding Indonesia’s sovereignty and sovereign rights in the North Natuna Sea. This study employs a qualitative approach with a descriptive research design. Data were collected through semi-structured interviews and documentation, consisting of primary data from informants involved in the formulation and implementation of defense policy, as well as secondary data from official documents, academic literature, and relevant regulations. Data were analyzed qualitatively through classification, categorization, interpretation, and triangulation of sources and methods. The findings reveal that Indonesia’s defense politics during 2014–2023 were carried out through an adaptive, measured, and integrative approach by combining defense posture strengthening, maritime patrols, law enforcement, defense diplomacy, and international legal legitimacy. This defense politics was relatively effective in preventing the establishment of China’s de facto control over Indonesia’s jurisdictional waters and in maintaining regional stability, although it still faced challenges such as power asymmetry, limited maritime capacity, the complexity of gray zone threats, and inter-agency coordination constraints.